Effect for Human Genomic Variation During the BMP4-Induced Conversion From Pluripotent Stem Cells to Trophoblast - Li, Hai-tao; Liu, Yajun; Liu, Hongde; Sun, Xiao (Frontiers in Genetics, 2020)
Role of genomic variation in differentiation has not been well understood yet. Here, the genomic variations were determined with the whole-genome sequencing for three pairs of pluripotent stem cell lines and their corresponding BMP4-induced trophoblast cell lines. We identified ~3,500 single nucleotide variations and ~4,500 indels by comparing the genome sequenced data between the stem cell lines and the matched BMP4-induced trophoblast cell lines, and annotated them by integrating the epigenomic and transcriptomic datasets. Relatively, introns enrich more variations. We found ~45% (42 genes) of the differentially expressed genes in trophoblasts that associate genomic variations. Six variations locate at transcription factors’ binding sites where H3K4me3 and H3K27ac are enriched in both H1 and H1_BMP4 were identified. And the epigenetic status around the genomic variations in H1 was similar to that in H1_BMP4. This means that the variation-associated gene’s expression change cannot be attributed to epigenetic alteration. The genes associated with the six variations were upregulated in differentiation. We inferred that during the differentiation, increased the expression level of gene MEF2C is due to a genomic variation, chromosomes 5: 88179358 A>G, which is at a binding site of TFs KLF16, NR2C2, and ZNF740 to MEF2C. Allele G shows a higher affinity to the TFs in the induced cells. The increased expression of MEF2C leads to an increased expression of TF MEF2C’s target genes, subsequently affecting the differentiation. Although genomic variation should not be a dominant factor in differentiation, we believed that genomic variation could indeed insert a role in the differentiation from the stem cells into trophoblast.